Isolate and diagnose the bacteria present in the hospital in the city of Diwaniyah and the statement of the mechanisms to control the use of antibiotics and antiseptics - A.P.Ali Abed Raheem AL-Nashi; Ghaidaa Raheem Lateef AL-Aosi (Al-Qadisiyah Journal of Pure Science, 2017)
The study included collection of 907 distributed environmental and clinical included 453 samples from hospital Diwaniya, the general education and 454 samples from the maternity hospital and children in the city of Diwaniya, for the period from the first of November 2010 until the end of April 2011 for the purpose of isolation and diagnosis of bacteria contaminated the hospitals and the extent of resistance of bacterial isolates to antibiotics and disinfectants. The bacterial isolates diagnosed from clinical specimens and environmental Hospital in Diwaniya, the general education has been reached (18) species bacteria during the study period. And were distributed among bacterial isolates to (4) types belonging to the genus Staphylococcus, including 89 isolates Ø°(29.99%) where bacteria included Staphylococcus aureus 68 Ceuta isolation of 22.8% and the isolation of Staphylococcus epidermidis 19 (6%), Staphylococcus warneri isolated one, and by (0.33%), while Staphylococcus hominis included only one isolate (0.33%)While the ((3 types belonging to the genus Streptococcus included (25) isolation (8.45%) included Streptococcus parasanguinis (1) isolation and by 0.33% and Streptococcus pneumoniae (17) isolation (5.7%), Streptococcus pyogenes (17) the isolation of 2.35%, while the Gender Pseudomonas sp. were included (29) isolation (9.76%) included the species Pseudomonas aeruginosa 16 isolation at a rate of 5.38% and Pseudomonas Pseudomonali 13 (4.3%), and also two types of sex spp. Enterobacter 19 isolates (6.39)% included Enterobacter aerogenes 11 isolates (3.7%) and Enterobacter cloacae 8 isolates (2.6%) and only one type for each of the races. Sphingomonas spp, Aeromonas spp, Bacillus spp, Serratia spp Acintobacter, spp, E.coli, Proteus and Klebsiella. The bacterial isolates diagnosed from clinical specimens and environmental Children's Hospital and childbirth education has been to isolate and diagnose 16 types of bacteria during the study period. And were distributed among bacterial species on the 3 types belonging to the genus Staphylococcus in 69 isolated at a rate of 31.22% included bacteria, Staphylococcus aureus 47 isolation (21%), Staphylococcus epidermidis 21 isolates) 9.5%) and Staphylococcus hominis (1) isolation (45. 0%) Also included two types of bacterial isolation affiliated Streptococcus isolates within 9 by 4.07% and included Streptococcus pneumoniae Azltan (0.90%), Streptococcus pyogenes (7) isolates (3.16%), and two belonging to the genus Pseudomonas sp. (19) isolation (8.59%) and two isolated Pseudomonas aeruginosa (18)( 8%) and Pseudomonas Pseudomonali one isolate (0.45%), and also two types of sex spp. Enterobacter 18 isolates (8.14%) included Enterobacter aerogenes 8 isolates (3.6%) and Enterobacter cloacae 10 isolates (4.5%) and one type for each of the races and and Aeromonas spp Bacillus spp Serratia spp and and E.coli and Proteus and Klebsiella. Also tested the sensitivity of bacterial isolates to (12) in an antibiotic is Amoxicillin and Penicillin and Ampicillin as hit ratios (80,71.2,68.2%) on respectively, while the recorded negative bacteria resistant to stain gram was (76.4,72.1,67.1,59.7%) of the anti-Amoxicillin and Ampicillin and Penicillin and Cefodizime respectively, also varied while the other isolates resistant to the antibiotic according to the nature and type of isolation tested. The test sensitivity of bacterial isolates to the disinfectants bacterial isolates have shown resistance to disinfectants varying by sex and type of bacteria and the type and concentration of disinfectant, Dettol disinfectant was Alsaadquis and focus 100% and 50% are the most efficient in controlling the bacterial isolates under study